Dance in the Diaspora: Kristin Jackson’s Life of Dance and the Migrant Body - Corpus, Rina Angela (Animo Repository, 2022)
This article is an account of Filipina-American choreographer Kristin Jackson’s dance history and selected repertoire. Jackson is one of the few Filipina dance artists based in the US who articulates her bi-cultural identity, and has created and performed a sustained body of works in both America and the Philippines, but whose aesthetics and history have yet to receive attention in dance studies and scholarship. I bring to the fore Jackson’s history and dance education in the light of being a migrant body from the Philippine postcolony, framing her dance career as migratory in nature, therefore embodying the liminal, ambulant diasporic experience, articulated in light of cultural research by Marie Alonzo-Snyder, Martin Manalansan and Fenella Cannel. I then locate Jackson in the general context of women’s autobiography in dance which coincided with a general trend in this thematic mode in American dance of that time, using Ann Cooper Albright’s research. I cull important snippets from various reviews of her choreography to give a general overview of the quality of her movement and choreographic aesthetic and impact. This essay further articulates aspects of her dance and cultural history together with her movement quality characterized by their multicultural roots. I argue that the diasporic Filipino self emerges and distinctly finds its mark in her body of work.